Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So far I have,

  • Let $d = (a,b)$
  • Which implies $d\mid a$ and $d\mid b$
  • Which implies there exist $x$ and $y$ such that $d\mid (a)(x) + (b)(y)$
  • So I want to find an $x$ and $y$ that can make the equation, $ax+by$ into $(a+1)(x)+(ab)(y)$
share|improve this question
2  
what if you let $a = 5$ and $b = 6$? –  user51427 Dec 9 '12 at 20:36
3  
I don't think that the statement is true. Try $a =2$ and $b = 3$. Then $(2,3) = 1$ but $(2+1, 2\times3) = (3,6) = 3$. Am I missing something? –  Tom Oldfield Dec 9 '12 at 20:37
1  
What about $(6,7)=1$ while $(7,42)=7$? (well, I was too late...) –  Hendrik Jan Dec 9 '12 at 20:38
4  
Maybe you mean $(a+b,ab)=1$ in the conclusion? –  Andres Caicedo Dec 9 '12 at 20:39
    
Anna: I edited your question. I tried to make the formatting more like what I think you had intended it to be. –  Thomas Dec 9 '12 at 20:40
show 2 more comments

2 Answers

if $b=a+1$ then the second gcd is $a+1$

share|improve this answer
    
what i mean is you square it and then you get a^2*x^2 + 2abxy +b^2y^2 and continue to manipulate it –  Cindy Dec 9 '12 at 20:47
3  
@Anna, the statement you are trying to prove is false. At this point, you should go back and check the source of the problem very carefully. –  Will Jagy Dec 9 '12 at 20:51
    
Anna = Cindy?${}$ –  Gerry Myerson Dec 11 '12 at 6:05
    
@GerryMyerson, yes, she changed it not long after I wrote this answer. I'm pretty sure she had time to see this. And, she has gone on to ask a bunch of questions at this level. I don't think she pays much attention after she posts things...I get it, also unregistered. –  Will Jagy Dec 11 '12 at 6:12
add comment

This answer gives $u,v$ with $abu+(a+b)v=1$, given $ax+by=1$.

Start with $ax=1-by$, subtract $ay$ from both sides, and get $$a(x-y)=1-(a+b)y.$$ Now start with $by=1-ax$, subtract $bx$ from both sides, and get $$b(y-x)=1-(a+b)x.$$ Now multiply these equations to get $$ab(x-y)(y-x)=1-(a+b)x -(a+b)y + (a+b)^2 xy,$$ which may be rearranged as $$ab(x-y)(y-x)+(a+b)(x+y-(a+b)xy)=1.$$ With $u=(x-y)(y-x)$ and $v=x+y-(a+b)xy$ this is $abu+(a+b)v=1.$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.